2020
DOI: 10.1177/0733464820968712
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Transition Interventions to Support Older Patients From Hospital to Home: A Systematic Scoping Review

Abstract: Background: Interventions supporting older adults’ transition from hospital to home can address geriatric needs. Yet this evidence base is fragmented. This review describes transitional interventions that provide pre- and post-discharge support for older adults and evaluates their implementation and effectiveness in improving health and well-being. Method: Articles were included if they examined the extent to which transitional interventions were effective in improving health and well-being outcomes and reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…Revisão de Literatura sobre a eficácia das intervenções de TC, para apoiar idosos do hospital para casa verificou que os que se beneficiaram de educação personalizada, com intervenções orientadas a metas que promovam sua capacidade de autocuidado, tiveram resultados mais eficientes de saúde e bem-estar. (32) Neste estudo, registou-se discordância de 51,92% para o item 12 e de 16,67% para o item 15. Resultado semelhante foi observado no sul do Brasil em pesquisa sobre a TC de pacientes com doenças crônicas, que também verificou maiores percentuais de discordância sobre uso de medicamentos e seus efeitos colaterais.…”
Section: Discussionunclassified
“…Revisão de Literatura sobre a eficácia das intervenções de TC, para apoiar idosos do hospital para casa verificou que os que se beneficiaram de educação personalizada, com intervenções orientadas a metas que promovam sua capacidade de autocuidado, tiveram resultados mais eficientes de saúde e bem-estar. (32) Neste estudo, registou-se discordância de 51,92% para o item 12 e de 16,67% para o item 15. Resultado semelhante foi observado no sul do Brasil em pesquisa sobre a TC de pacientes com doenças crônicas, que também verificou maiores percentuais de discordância sobre uso de medicamentos e seus efeitos colaterais.…”
Section: Discussionunclassified
“…The assessment of participation should begin during hospitalization to enable early identification and to improve the transition process from the hospital to the community. Indeed, goal-directed transition interventions that are designed to meet older patient's unique needs were previously recommended (O'Donnell et al, 2021), and maintaining participation can serve as their ultimate goal.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last couple of decades, research has shown diverging effects on readmission and mortality among older medical patients. Some studies have reported positive impacts, while others have reported no or negative impacts [17,18,[33][34][35][36][37]. Other studies found major implementation bottlenecks due to lack of resources, and information and organisational problems [38,39].…”
Section: Comparison With Previous Researchmentioning
confidence: 99%